Designing a novel visible-light-driven heterostructure Ni–ZnO/S-g-C3N4 photocatalyst for coloured pollutant degradation. Issue 58 (12th November 2021) - Bahadur, Ali; Iqbal, Shahid; Alsaab, Hashem O.; Awwad, Nasser S.; Ibrahium, Hala A.
Abstract : Ni-doped ZnO/S-g-C3 N4 nanocomposites were formed as a novel heterostructure photocatalyst. Abstract : In this study, photocorrosion of ZnO is inhibited by doping Ni in the ZnO nanostructure and electron–hole recombination was solved by forming a heterostructure with S-g-C3 N4 . Ni is doped into ZnO NPs from 0 to 10% (w/w). Among the Ni-decorated ZnO NPs, 4% Ni-doped ZnO NPs (4NZO) showed the best performance. So, 4% Ni–ZnO was used to form heterostructure NCs with S-g-C3 N4 . NZO NPs were formed by the wet co-precipitation route by varying the weight percentage of Ni (0–10% w/w). Methylene blue (MB) was used as a model dye for photocatalytic studies. For the preparation of the 4NZO- x -SCN nanocomposite, 4NZO NPs were formed in situ in the presence of various concentrations of S-g-C3 N4 (10–50% (w/w)) by using the coprecipitation route. The electron spin resonance (ESR) and radical scavenger studies showed that O2 − and OH free radicals were the main reactive species that were responsible for MB photodegradation.